The Development of English Language Skills in Early Childhood Education - Nanda Dwi Astri; Muhammad Walimsyah Sitorus; Gumarpi Rahis Pasaribu (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to explore the development of English language skills in early childhood education, focusing on how young learners acquire basic language abilities in classroom settings. The research is grounded in the increasing importance of English as a global language and the need to introduce it at an early age. However, teaching English to young learners presents unique challenges due to their developmental characteristics, limited attention span, and varying learning abilities. Therefore, this study investigates the processes, strategies, and factors that influence children’s English language development, particularly in terms of vocabulary acquisition, pronunciation, and simple sentence construction. This study employed a qualitative descriptive approach with a case study design conducted in an early childhood education institution in Indonesia. The participants consisted of children aged 4–6 years and an English teacher selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using thematic analysis, including data reduction, coding, categorization, and interpretation to identify patterns related to language development. To ensure the trustworthiness of the findings, triangulation and member checking techniques were applied. The findings reveal that children’s English language development occurs gradually through engaging and interactive learning activities such as songs, games, and storytelling. These activities help children improve their vocabulary, pronunciation, and ability to form simple expressions. The teacher plays a significant role in facilitating learning by using repetition, visual aids, and contextual teaching strategies. Additionally, a supportive and enjoyable learning environment enhances children’s motivation and participation. However, limited exposure to English outside the classroom and differences in individual abilities were identified as challenges affecting language development.